PENGARUH MEDIA APLIKASI MACROMEDIA DIRECTOR MX 2004 TERHADAP HASIL BELAJAR SISWA KELAS X PADA MATA PELAJARAN KOMPUTER DAN JARINGAN DASAR - Kantari, Ade; Baysa, Muh. Husein (UNDIKMA, 2019)
Abstract. The problem that occurs is the teaching and learning activities in the classroom centeredon the media used by the teacher. The media used by teachers for presentations is to only usedpowerpoint applications that contain theories only, and teachers also sometimes used the lectureand question and answer method, when delivered material. So students do not understand thematerial presented by the teacher. The purpose of this study was to determine The Effect ofMacromedia Director MX 2004 Application Media Towards Students’ Outcomes Class X inComputer Subjects and Basic Networks at SMKN 1 Lingsar, West Lombok Regency in AcademicYear 2019/2020.. Data collection techniques in this study used the test as the main method whiledocumentation and observation as a complement. Data analysis techniques in this study used the ttest formula. The results obtained from the results of the t-test showed the t-test of 43.85, thenbased on a significant level of 5% and N = 37 it turned out that the amount of the rejection of thenull hypothesis stated in the table was 2.042. This statement shows that the t-test value was greaterthan t-table (43.85> 2.042), because t-test was greater than t-table, this research was said to besignificant. This means that the null hypothesis was rejected and the alternative hypothesis wasaccepted which reads: There was The Effect of Macromedia Director MX 2004 Application MediaTowards Students’ Outcomes Class X in Computer Subjects and Basic Networks at SMKN 1Lingsar, West Lombok Regency in Academic Year 2019/2020., so it can be concluded that theresults of this study are “significant”.